The concept of guerrilla warfare in Lithuania in the 1920—1930s - Jokubauskas Vytautas (Baltic Region, 2012)
This article analyses the military and tactical training of the members of the Lithuanian Riflemen’s Union for guerrilla warfare in the interwar period. Small nations, such as Lithuania and other Baltic states, being unable to build up military strength in order to ensure national security, were forced to seek for unconventional methods of warfare, including guerrilla strategies. The study places emphasis on the development of the guerrilla war concept in the Union periodicals. The author retraces a change in the intensity of the guerrilla warfare concept propagation amongst Lithuanian population and riflemen, in particular, through publications in the Trimitas — a periodical of the Lithuanian Riflemen’s Union. The author also identifies the narratives associated with the guerrilla matters employed for propaganda purposes in order to create an image of a guerrilla as a defender of the Homeland — Lithuania. Additionally, the structure and numbers of the Union are analysed through a comparison with similar organisations of the other «small nations» of the Baltic North-East. The author addresses the issue of military missions planned by the Lithuanian Army, as well as the way riflemen implemented them. Since the Union did not only offer military training, but was also engaged in the patriotic propaganda, the article focuses on the network of cultural institutions, homes of riflemen, orchestras, libraries, choirs, and athletic clubs used by the Union. The article sets out to establish whether the loss of Lithuanian sovereignty could have been possible without giving rise to a protracted guerrilla war.